Interim equilibrium implementation - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2014)
A social choice rule is said to be implementable if one can design a mechanism(or institution) in which the set of outcomes prescribed by a given solutionconcept coincides with that specified by the social choice rule. I adoptinterim equilibrium (i.e., Bayesian Nash equilibrium where each agent’s interimbeliefs do not necessarily admit a prior) as the solution concept andinvestigate the corresponding implementation problem in general incompleteinformation environments. I identify arguably the weakest set of conditionsunder which implementation in interim equilibrium is possible. By doingso, I also unify the literature of the so-called Bayesian implementation andNash implementation.